2020
DOI: 10.1097/scs.0000000000006016
|View full text |Cite
|
Sign up to set email alerts
|

Latissimus Dorsi-Myocutaneous Flap in the Repair of Titanium Mesh Exposure and Scalp Defect After Cranioplasty

Abstract: Titanium mesh was widely used for cranium defect repair but associated with high complication rates. In this study, the authors describe a method using latissimus dorsi-myocutaneous flap in the repair of titanium mesh exposure and scalp defect after cranioplasty, and the plate retaining is also achieved. Fifteen patients from April 2012 to May 2016 underwent this procedure, the age ranged from 32 to 62 years and 47 years old on average, and all the patient had plate exposure combined with surgical site infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Robust soft tissue coverage is necessary to re‐establish the barrier that shields the brain from external pathogens, and secondarily restore an aesthetic appearance. The use of vascularized muscle free flaps to treat large scalp and cranial defects has been well‐described in recent studies (Dong et al, 2020; Lin et al, 2014; Ray et al, 2020). A muscle flap has the advantage of an abundant vasculature, and thus can resist infection, and has the potential to thicken the atrophied scalp and fill in the dead space.…”
Section: Discussionmentioning
confidence: 99%
“…Robust soft tissue coverage is necessary to re‐establish the barrier that shields the brain from external pathogens, and secondarily restore an aesthetic appearance. The use of vascularized muscle free flaps to treat large scalp and cranial defects has been well‐described in recent studies (Dong et al, 2020; Lin et al, 2014; Ray et al, 2020). A muscle flap has the advantage of an abundant vasculature, and thus can resist infection, and has the potential to thicken the atrophied scalp and fill in the dead space.…”
Section: Discussionmentioning
confidence: 99%
“…Standard management of skin defects with titanium mesh exposure involves wound debridement, and removal or exchange of implants to prevent secondary infection and to achieve suitable aesthetic outcomes [6,11]. Appropriate coverage with skin flaps, such as forehead muscle flaps, temporal island flaps and LD free flaps should be performed afterwards [2,12]. However, few studies have described cases of recurrent skin defects from not completely removing the titanium mesh.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The LD flap has a large harvesting area, and there is no need to locate the perforators. (2) Some authors have reported that if the wound is covered at an early stage, the risk of infection is lower (Dong et al, 2020; Ju et al, 2018). In our case series, no wound infection or osteomyelitis was recorded in any patient during the follow‐up period.…”
Section: Discussionmentioning
confidence: 99%